Constituents of Artemisia gmelinii Weber ex Stechm. from Uttarakhand Himalaya: A Source of Artemisia Ketone - Haider, S. Z. (Medknow Publications & Media Pvt Ltd, 2012)
The essential oils isolated from the aerial parts of two different populations of Artemisia gmelinii growing in Uttarakhand Himalaya region were analysed by gas chromatography and gas chromatography/mass spectrometry (GC-MS) in order to determine the variation of concentration in their constituents. Artemisia ketone was detected as a major constituent in both the populations i.e., Niti valley and Jhelum samples. Niti oil was found to have considerably greater amounts of artemesia ketone (53.34%) followed by α-thujone (9.91%) and 1,8-cineole (6.57%), Similarly, the first major compound in Jhelum oil was artemesia ketone (40.87%), whereas ar-curcumene (8.54%) was identified as a second major compound followed by α-thujone (4.04%). Artemisia ketone can be useful for perfumery and fragrance to introduce new and interesting herbaceous notes.